Evidence Head Tilt Has Dissociable Effects on Dominance and Trustworthiness Judgments, But Does Not Have Category-Contingent Effects on Hypothetical Leadership Judgments. (February 2020) - Torrance, Jaimie S.; Holzleitner, Iris J.; Lee, Anthony J.; DeBruine, Lisa M.; Jones, Benedict C.
Previous research has found that physical characteristics in faces that influence perceptions of trustworthiness and dominance have context-contingent effects on leadership perceptions. People whose faces are perceived to be trustworthy are judged to be better leaders in peacetime contexts than wartime contexts. By contrast, people whose faces are perceived to be dominant are judged to be better leaders in wartime contexts than peacetime contexts. Here, we tested for judgment-contingent (dominance vs. trustworthiness) effects of head tilt (i.e., head pitch rotation) on person perception and context-contingent (peacetime vs. wartime) effects of head tilt on leadership judgments. Although we found that head tilt influenced judgments of trustworthiness and dominance (Study 1), head tilt did not influence leadership judgments (Study 2). Together, these results suggest that the context-contingent effects of physical characteristics on leadership judgments reported in previous work do not necessarily extend to head tilt, even though head tilt influences perceptions of trustworthiness and dominance.